Concise Review: Multipotent Mesenchymal Stromal Cells in Blood - He, Qiling; Wan, Chao; Li, Gang (Stem cells (Dayton, Ohio), 2007)
Peripheral blood‐derived multipotent mesenchymal stromal cells circulate in low number. They share, most although not all, of the surface markers with bone marrow‐derived multipotent mesenchymal stromal cells, possess diverse and complicated gene expression characteristics, and are capable of differentiating along and even beyond mesenchymal lineages. Although their origin and physio‐pathological function are still unclear, their presence in the adult peripheral blood might relate to some interesting but controversial subjects in the field of adult stem cell biology, such as systemic migration of bone marrow‐derived multipotent mesenchymal stromal cells and the existence of common hematopoietic‐mesenchymal precursors. In this review, current studies/knowledge about peripheral blood‐derived multipotent mesenchymal stromal cells is summarized, and the above‐mentioned topics are discussed.